From Growth Mindset to Grit in Chinese Schools: The Mediating Roles of Learning Motivations - Zhao, Yukun; Niu, Gengfeng; Hou, Hanchao; Zeng, Guang; Xu, Liying; Peng, Kaiping; Yu, Feng (Frontiers in Psychology, 2018)
Growth mindset and grit have attracted much attention in educational research recently. Yet the underlying mechanisms that relate these variables to each other as well as to many other variables remain largely unclear. This study investigates the relationships among growth mindset, learning motivation, grit, and school engagement. We recruited a total of 1,842 students (884 males and 958 females) from third to ninth grade in a Chinese city. Results from the structural equation model analyzing the students’ responses showed that learning motivation partially mediates the relationship between growth mindset and grit, and grit partially mediates the relationship between learning motivation and school engagement. Specifically, intrinsic motivation and identified regulation of extrinsic motivation are positively associated with growth mindset, grit, and school engagement while external regulation of extrinsic motivation is negatively associated with the same three variables. Additionally, introjected regulation of extrinsic motivation is uncorrelated with these three variables. This study furthers the understanding of the underlying mechanisms through which growth mindset and grit positively impact education.